2019
DOI: 10.1016/j.cstp.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors affecting bicycle sharing system acceptability in a developing country: The case of Mashhad, Iran

Abstract: The aim of this study is to investigate the factors affecting the acceptability of a bicycle sharing system (BSS) in Mashhad, which is the first BSS to be introduced in Iran. Given the low usage rated of the BSS, we distributed a survey in all stations. 134 users answered the questionnaire. We clustered the potentially relevant factors in five dimensions: Socio-cultural, Economic, Infrastructure, System function and Environmental. We eliminated the Environmental dimension because of invalid loading factors. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…Most of the users in our study have a low to medium income, in contrast to other previous studies on BSSs which showed higher rates of adoption among higher income residents (Transport for London, 2010; Ogilvie and Goodman, 2012;Fishman et al, 2014;Fishman et al, 2015;Ricci, 2015;Raux et al, 2017;Hosford et al, 2018). The differences between BSSs in developing and developed countries in terms of users' income was discussed recently by Jahanshahi et al (2019b), where it seems using a BSS is more reasonable in developing countries and contexts which have higher costs associated with of transportation and cars. In addition, another potential barrier which could be related to the sociocultural context, may be social status, where people with higher incomes avoid using BSSs because of a perceived potential decline in social status they use an inexpensive mode of transport.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Most of the users in our study have a low to medium income, in contrast to other previous studies on BSSs which showed higher rates of adoption among higher income residents (Transport for London, 2010; Ogilvie and Goodman, 2012;Fishman et al, 2014;Fishman et al, 2015;Ricci, 2015;Raux et al, 2017;Hosford et al, 2018). The differences between BSSs in developing and developed countries in terms of users' income was discussed recently by Jahanshahi et al (2019b), where it seems using a BSS is more reasonable in developing countries and contexts which have higher costs associated with of transportation and cars. In addition, another potential barrier which could be related to the sociocultural context, may be social status, where people with higher incomes avoid using BSSs because of a perceived potential decline in social status they use an inexpensive mode of transport.…”
Section: Discussioncontrasting
confidence: 67%
“…The bicycles in the BSS are of poor quality and do not have suitable and high quality equipment. Previous studies on BSS in Mashhad found that quality and quantity of bicycle lane strongly influence BSS usage in this city (Jahanshahi et al, 2018(Jahanshahi et al, , 2019b. Therefore, Perceived Safety was added as a sixth (new) construct for the UTAUT model.…”
Section: Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research we found consistently shows that bikeshare and e-scooter users are younger than the population generally, with seventeen studies providing such data for bikeshare (Soltani et al 2019; Hess and Schubert 2019; Murphy and Usher 2015; Woodcock et al 2014; Vogel et al 2014; Jahanshahi, van Wee, and Kharazmi 2019; Fishman et al 2014; Wielinski, Trépanier, and Morency 2017a; Shaheen et al 2012a; Guo et al 2017; Shaheen, Christensen, and de Lima 2015; Xin et al 2018; Hosford et al 2018; Buck et al 2013; LDA Consulting 2012; Kaviti, Venigalla, and Lucas 2019b; Gavin et al 2016) and six for e-scooters (San Francisco Municipal Transportation Agency 2019; Orr, MacArthur, and Dill 2019; Mobility Lab 2019; City of Santa Monica 2019; Baltimore City 2019; City of Minneapolis 2019). These patterns are consistent with age differences in bicycling generally in low-cycling countries (Pucher and Buehler 2012).…”
Section: Access To and Use Of Vehicle Sharing By Different Populationssupporting
confidence: 62%